Low-temperature, Selective Catalytic Deoxygenation of Vegetable Oil in Supercritical Fluid Media - Kim, Seok Ki; Lee, Hong-shik; Hong, Moon Hyun; Lim, Jong Sung; Kim, Jaehoon (WILEY-V C H VERLAG GMBH, 2014)
The effects of supercritical fluids on the production of renewable diesel-range hydrocarbons from natural triglycerides were investigated. Various supercritical fluids, which included CO2 (scCO(2)), propane (scC(3)H(8)) and n-hexane (scC(6)H(14)), were introduced with H-2 and soybean oil into a fixed-bed reactor that contained pre-activated CoMo/gamma-Al2O3. Among these supercritical fluids, scC(3)H(8) and scC(6)H(14) efficiently allowed the reduction of the reaction temperature by as much as 50 degrees C as a result of facilitated heat and mass transfer and afforded similar yields to reactions in the absence of supercritical fluids. The compositional analyses of the gas and liquid products indicated that the addition of scC(3)H(8) during the hydrotreatment of soybean oil promoted specific deoxygenation pathways, decarbonylation and decarboxylation, which consumed less H-2 than the hydrodeoxygenation pathway. As a result, the quantity of H-2 required to obtain a high yield of diesel-range hydrocarbons could be reduced to 57% if scC(3)H(8) was used. As decarboxylation and decarbonylation are mildly endothermic reactions, the reduced heat transfer resistance in scC(3)H(8) may drive the deoxygenation reaction to thermodynamically favourable pathways.